The Areas of Unfavourable Demographic Processes in Eastern Poland — Selected Aspects - Bański, Jerzy; Flaga, Małgorzata (Regional Barometer. Analyses & Prognoses, 2013)
Population factors are the most important elements of the socio-economic development of regions. Contemporary structure of population in Eastern Poland is the result of post-war changes, mainly in the field of natural growth and migration. The goals of this article are to assess the present trends of population change in the regions of Eastern Poland and to identify the areas that are characterized by negative effects of selected phenomena. It is also an important research issue to identify the main causes of negative processes shaping the population.